Comparative Analysis of Tourism Development at The Example of Selected EU Countries - Natalia ZNAMIEROWSKA; Milena BERA (Communications of International Proceedings, 2025)
This article presents an analysis of tourism development in selected European Union countries. The study was motivated by the need to analyze changes in tourism development in individual European Union (EU) countries following the COVID-19 pandemic. The article is an attempt to fill the research gap in the field of changes in tourism development in recent years and to identify factors determining the development of tourism. Over the past few decades the changes has been observed in leisure activities and travel. This is driven not only by ecnomic and technological but also by demographic changes. Tourism is undergoing countinuous shifts, stemming from shifts in tourist expactations and modifinig trends in tourist stays. Nowadays, tourists increasingly expect personalized tourism experiences. The COVID-19 pandemic has caused particularly significant transforms in the tourism market. The aim of the article is to conduct a comparative analysis of tourism development in selected EU countries, indicating changes in the years 2018-2024. The article analyzes secondary data from the EUROSTAT database and domestic and international literature. The analysis showed significant changes in the tourism market caused by the COVID-19 pandemic, which was reflected in the decrease in the number of tourist arrivals and a reduction in the number of tourist facilities. In 2020, there was a particularly strong reduction in tourist traffic in the countries surveyed, with the largest decline in arrivals of foreign tourists. Despite this, an increase in domestic travel percentage was observed during the pandemic (this was particularly noticeable in 2020 – with the exception of Greece, which was still visited more often by foreign tourists than domestic ones).This study serves as a starting point for further analysis of changes in tourism development in the European Union.
Keywords: tourism development; tourism